Anatomical Dimensions and Types of the Anterior Clinoid Process in Libyan population by Using Computed Tomography: A cross Sectional Study - Fatimah Alhadi; Seraj ALzentani; Iman Ayad; Alia Ashmeisa; Abdullah Bashir; Ibrahim Tayib; Amal Alfakhr (AlQalam Journal of Medical and Applied Sciences, 2024)
The anterior clinoid process (ACP) has a complex anatomical feature and surrounded by important structures which may complicate the surgical procedures during the anterior clinoidectomy. Our objective was to measure dimensions of anterior clinoid process, and to determine variations of its types. Forty-nine of cranial computed tomography scans were performed from adult Libyan patients on routine examination of paranasal sinus at Benghazi Medical Center between February 1, 2023, and April 14, 2023. The right and left ACP length and the base width were measured on the axial CT images. Data analysis was done using SPSS version 23. The means and standard deviations were calculated. The paired Student’s t test was used to determine the statistically significant differences in means between the right and left ACP. (P ≤ 0.05) was considered statistically significant at (95%) confidence interval. The length of the right and left ACPs were 11.2 ± 2.2 mm and 11.6 ± 2.4mm, respectively. The width of the right and left ACPs were 5.37± 1.22 mm and 5.42 ± 1.24mm, respectively. Type 2 anterior clinoid process was the commonest (75.5 %) while type 1 was the least common (4.1 %). There was no statistically significant difference between right and left sided measurements. Our study outcomes may be helpful for pre-operative planning. Presence of any variations may result in unnecessary injury to the complicated surgical procedures that involve removal of ACPs. Further research studies required with large sample size of population will give well understanding about the parameter of ACPs. النَّاتِئُ السَّريرِيُّ الامامي له مواصفات تشريحية معقدة ومحاط بتركبيات مهمة قد تؤدي إلى تعقيد العمليات الجراحية أثناء استئصال النَّاتِئُ السَّريرِيُّ الامامي. كان هدفنا هو قياس أبعاد الناتئ السريري الأمامي وتحديد الاختلافات في أنواعه. تم إجراء تسعة وأربعين فحصًا بالتصوير المقطعي للجمجمة على مرضى ليبيين بالغين أثناء الفحص الروتيني للجيوب الأنفية في مركز بنغازي الطبي في الفترة ما بين 1 فبراير 2023 و14 أبريل 2023 وتم قياس الطول و العرض للنَّاتِئُ السَّريرِيُّ الامامي الأيمن والأيسر على الصور المقطعية وتحليل البيانات باستخدام البرنامج الاحصائى إصدار 23 و حساب المتوسطات والانحرافات المعيارية و استخدام اختبار الطالب المقترن لتحديد فروق ذات دلالة إحصائية بين النَّاتِئُ السَّريرِيُّ الامامي الأيمن والأيسر وكانت النتائج كالاتي: طول النَّاتِئُ السَّريرِيُّ الامامي الأيمن والأيسر 11.2 ± 2.2 مم و11.6 ± 2.4 مم على التوالي و كان عرض النَّاتِئُ السَّريرِيُّ الامامي الأيمن والأيسر 5.37 ± 1.22 مم و5.42 ± 1.24 مم على التوالي. كان النوع الثاني من الناتئ السريري الأمامي هو الأكثر شيوعاً (75.5%) بينما كان النوع الأول هو الأقل شيوعاً (4.1%). لم يكن هناك فروق ذات دلالة إحصائية بين القياسات على الجانب الأيمن والأيسر. تعتبر نتائج هده الدراسة مفيدة للتخطيط قبل الجراحة. وتؤكد الدراسة علي ان وجود أي اختلافات قد يؤدي إلى إصابات يمكن الاستغناء عنها اثناء العمليات الجراحية .المزيد من الدراسات البحثية مع حجم عينة كبير من السكان سيعطى فهما جيدا عن المعايير للنَّاتِئُ السَّريرِيُّ الامامي